TNFα-Signaling Modulates the Kinase Activity of Human Effector Treg and Regulates IL-17A Expression - Urbano, Paulo C. M.; He, Xuehui; Heeswijk, Bennie van; Filho, Omar P. S.; Tijssen, Henk; Smeets, Ruben L.; Joosten, Irma; Koenen, Hans J. P. M. (Frontiers in Immunology, 2020)
Maintenance of regulatory T cells CD4+CD25highFOXP3+ (Treg) stability is vital for proper Treg function and controlling the immune equilibrium. Treg cells are heterogeneous and can reveal plasticity, exemplified by their potential to express IL-17A. TNFα-TNFR2 signaling controls IL-17A expression in conventional T cells via the anti-inflammatory ubiquitin-editing and kinase activity regulating enzyme TNFAIP3/A20 (tumor necrosis factor-alpha-induced protein 3). To obtain a molecular understanding of TNFα signaling on IL-17 expression in the human effector (effTreg, CD25highCD45RA−) Treg subset, we here studied the kinome activity regulation by TNFα signaling. Using FACS-sorted naïve (naïveTreg, CD25highCD45RA+) and effTreg subsets, we demonstrated a reciprocal relationship between TNFα and IL-17A expression; effTreg (TNFαlow/IL-17Ahigh) and naïveTreg (TNFαhigh/IL-17Alow). In effTreg, TNFα-TNFR2 signaling prevented IL-17A expression, whereas inhibition of TNFα signaling by clinically applied anti-TNF antibodies led to increased IL-17A expression. Inhibition of TNFα signaling led to reduced TNFAIP3 expression, which, by using siRNA inhibition of TNFAIP3, appeared causally linked to increased IL-17A expression in effTreg. Kinome activity screening of CD3/CD28-activated effTreg revealed that anti-TNF-mediated neutralization led to increased kinase activity. STRING association analysis revealed that the TNF suppression effTreg kinase activity network was strongly associated with kinases involved in TCR, JAK, MAPK, and PKC pathway signaling. Small-molecule-based inhibition of TCR and JAK pathways prevented the IL-17 expression in effTreg. Together, these findings stress the importance of TNF-TNFR2 in regulating the kinase architecture of antigen-activated effTreg and controlling IL-17 expression of the human Treg. These findings might be relevant for optimizing anti-TNF-based therapy and may aid in preventing Treg plasticity in case of Treg-based cell therapy.